Implementasi Metode Design Thinking Dalam Perancangan Prototype Sistem Pengelolaan Data Barang - Anggraini, Dini; Hamdani, Dani (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
The design of the UI of the Information System for managing goods data is a system interface design that is used to manage input, output, and recapitulation of goods for inventory, so as to minimize human error and minimize loss of goods data. The problem occurs in the current business process, namely for managing data on incoming goods and outgoing goods only recorded in book archives. So that it often experiences problems in calculating goods and takes time to get information about goods data that is not in accordance with availability. The purpose of this research is to design a goods data management system UI, which can manage data and stock items using the Design Thinking method which will be applied at CV. XYZ. The result of this research is a UI design that operates to support the business processes of the warehouse section, so that managing requests for purchasing goods to suppliers can be more accurate, searching for goods data can optimize time, and help the process of supplying and selling goods to consumers.Keywords: Design Thinking, Goods Data, User Interface